Rancangan Kriteria Sustainability untuk Evaluasi Strategic Supplier di Industri Otomotif X dengan Metode QFD - Putri Mety Zalynda; Rajesri Govindaraju; Andi Cakravastia; Kadarsah Suryadi; Bram Andryanto (Journal of Research in Industrial Engineering and Management, 2023)
The strategic supplier evaluation process is a decision-making problem that has many criteria and objectives related to both qualitative and quantitative factors. In the strategic supplier evaluation process, the Quality Function Deployment (QFD) method can translate issues of critical stakeholder needs, starting from conceptual needs into several strategic supplier evaluation criteria that can be used as a reference. One of the most important pieces of information is that by using the QFD method, the weight of the evaluation criteria is derived from the ranking of the importance of stakeholder needs together with the weight of the relationship between stakeholder requirements and evaluation criteria. According to the results of the literature study, most previous studies used economic criteria with a single stakeholder. This research will use sustainability criteria with multi-stakeholders. This research will design the selection of sustainability criteria for evaluating strategic suppliers for the PT X automotive industry in Indonesia using the QFD method. The results of the second House of Quality (HOQ) from QFD, are twenty sustainability criteria for evaluating strategic suppliers for the automotive industry.